Trapping and detection of single viruses in an optofluidic chip - Shi, Yuzhi (2022)
Accurate single virus detection is critical for disease diagnosis and early prevention, especially in view of current pandemics. Numerous detection methods have been proposed with the single virus sensitivity, including the optical approaches and immunoassays. However, few of them hitherto have the capability of both trapping and detection of single viruses in the microchannel. Here, we report an optofluidic potential well array to trap nanoparticles stably in the flow stream. The nanoparticle is bound with single viruses and fluorescence quantum dots through an immunolabeling protocol. Single viruses can be swiftly captured in the microchannel by optical forces and imaged by a camera. The number of viruses in solution and on each particle can be quantified via image processing. Our method can trap and detect single viruses in the 1 mL serum or water in 2 h, paving an avenue for the advanced, fast, and accurate clinical diagnosis, as well as the study of virus infectivity, mutation, drug inhibition, etc.